Exploring naltrexamine derivatives featuring azaindole moiety via nitrogen-walk approach to investigate their in vitro pharmacological profiles at the mu opioid receptor. (1st June 2021) - Ma, Hongguang; Wang, Huiqun; Gillespie, James C.; Mendez, Rolando E.; Selley, Dana E.; Zhang, Yan
Graphical abstract: Application of nitrogen-walk approach maintained excellent binding affinity and conferred significant function switch at the MOR. Abstract: In the present work, we reported the application of a nitrogen-walk approach on developing a series of novel opioid ligands containing an azaindole moiety at the C6-position of the epoxymorphinan skeleton. In vitro study results showed that introducing a nitrogen atom around the indole moiety not only retained excellent binding affinity, but also led to significant functional switch at the mu opioid receptor (MOR). Further computational investigations provided corroborative evidence and plausible explanations of the results of the in vitro studies. Overall, our current work implemented a series of novel MOR ligands with high binding affinity and considerably low efficacy, which may shed light on rational design of low efficacy MOR ligands for opioid use disorder therapeutics.